Secure and efficient routing protocol for low-power and lossy networks for IoT networks - Soukayna Riffi Boualam; Mariya Ouaissa; Mariyam Ouaissa; Abdellatif Ezzouhairi (Institute of Advanced Engineering and Science, 2022)
R outing p rotocol for l ow p ower and l ossy (RPL) is destined to support the specific requirements of l ow p ower and l ossy n etworks (LLN). This type of network suffers from the problem of determining and securing a routing protocol to best suit an environment. This article aims to present a new version of the efficient and secure RPL protocol. The proposed scheme consists of two parts : i) Proposing a new o bjective f unction (OF) based RPL which combines three nodes and links metrics are: e xpected r etransmission n umber (ETX), h ope c ount (HC), and the residual energy in order to have a precise decision to c hoose the optimal way to the des tination. ii) To securing the new efficient RPL protocol by combining an improved Diffie - Hellman (DH) algorithm for a robust key exchange model with k eyed - h ash m essage a uthentication c ode (HMAC) to ensure the authentication and integrity of RPL data exchan ged. To verify the level of security, we apply a formal verification using AVISPA tool which indicate that the s ecure and e fficient RPL (SE-RPL) achieve all security requirements. Simulation results on the Contiki platform illustrate that our proposed is m ore efficient in terms of p acket d elivery r atio (PDR) and energy compared to others standard OF.